IDENTIFICATION OF TOURISM POTENTIALS IN CATUR VILLAGE KINTAMANI - Putu Chris Susanto; Anak Agung Kompiang Adiada; Ni Luh Christine P. Suyasa (Seminar Ilmiah Nasional Teknologi, Sains, dan Sosial Humaniora (SINTESA), 2018)
ABSTRACTThe community of Catur Village in Kintamani aims to initiate a community-based tourism program (CBT) based on the potential tourist attractions the village possesses, namely coffee plantations, unique culture, and captivating nature in the central mountains of Bali. This study seeks to identify the tourism potentials in Catur Village based on ‘4A’ (Attraction, Accessibility, Amenity and Ancillary Services), and identify the challenges in starting CBT by using PESTLE Analysis. This study utilizes descriptive analysis with qualitative approach. The findings of this study indicate several highly potential tourism attractions in Catur Village. The first is the potential for agro-tourism in the coffee, orange and marigold plantations. There is also potential for eco-tourism in Segeha Waterfall and the hills surrounding the village. Catur Village also has potential culture tourism attractions with the existence of the unique blend of Balinese and Chinese Peranakan cultures in Banjar Lampu and Pura Pebini that has intimate relation with the legend of Dewi Danu and Jaya Pangus. But those attractions are not yet supported with adequate aspects of accessibility, amenity and ancillary services, particularly in terms of accommodation and other supporting facilities.Keywords: tourism, tourist destination, development, village, community-based tourismABSTRAKMasyarakat Desa Catur, Kecamatan Kintamani mencanangkan program pariwisata berbasis masyarkat dalambentuk desa wisata berdasarkan potensi wisata yang ada di desa tersebut, terutama perkebunan kopi, budaya yang unik, dan pemandangan alam yang indah di wilayah pengunungan yang terletak di tengah-tengah pulau Bali. Artikel ini membahas potensi wisata di Desa Catur berdasarkan konsep ‘4A’ (Atraksi, Aksesibilitas, Amenitas, dan Ancillary Services), serta mengidentifikasi tantangan yang dihadapi dalam memulai program desa wisata dengan mengunakan alat analisis PESTLE, dengan melakukan analisis deskriptif dengan pendekatan kualitatif. Temuan dalam penelitian ini mengindentifikasikan beberapa potensi wisata yang menjanjikan di Desa Catur, antara lain wisata agro berupa perkebunan kopi, jeruk, dan bunga gumitir. Di samping itu, Desa Catur juga memiliki potensi ekowisata di Air Terjun Segeha dan perbukitan di sekitar desa, yang dilengkapi dengan penggabungan budaya Bali dan budaya Peranakan Tionghoa yang unik di Banjar lampu, serta wisata rohani di PuraPebini yang memiliki hubungan erat dengan legenda Dewi Danu dan Jaya Pangus.Namun potensi wisata tersebut belum didukung oleh aspek-aspek lain termasukakses, amenitas, dan ancillary services yang memadai, terutama dalam halakomodasi bagi pengunjung.Kata kunci: pariwisata, desa wisata, destinasi wisata, pariwisata berbasismasyarakat